Case Report: Bowen’s disease treated with PD-1 inhibitor and chemotherapy - Xie, Xiaohui; Chen, Qinyang; Zhang, Jian; Peng, Xiaodong (Frontiers in Oncology, 2025)
A 51-year-old man with perianal Bowen’s diseases, treated with tislelizumab and capecitabine chemotherapy, the tumor was significantly reduced and Improved quality of life.